Achieving a healthy indoor environment by using an emissions barrier to stop the spread of chemicals from a building into the indoor air. Issue 4 (17th March 2022) - Larsson, Lennart; Mattsson, Johan
Abstract : An emissions barrier was used in a premises due to complaints about the indoor air quality (IAQ) as a result of emissions from the building in question. The emissions comprised chlorophenols/chloroanisoles and polycyclic aromatic hydrocarbons (PAH) from treated wood and volatile organic compounds (VOCs), mainly 2-ethylhexanol, from polyvinyl chloride (PVC) flooring and the glue used to paste the flooring onto a concrete slab. Attaching the barrier at the surfaces from where the emissions were spread (floor, walls, ceilings) resulted in a fresh and odour-free indoor air. We conclude that using an emissions barrier in buildings made unhealthy by moisture is an efficient way of restoring pleasant and healthy indoor air.